Falling Through the Cracks: How the Community-Based Approach Has Failed Calgary’s Chronically Homeless - Katrina Milaney (The School of Public Policy Publications, 2018)
The seeds of chronic homelessness, with the addictions and mental illness that often accompany it, are sown frequently in traumatic childhoods. A survey of 300 people experiencing chronic homelessness and those sleeping rough in Calgary reveals that these individuals have suffered childhood trauma at a rate five times higher than the general population. Those traumas include neglect, parents with addiction issues, domestic violence and abuse. Unfortunately for those seeking help, community-based services in Calgary have been unable to keep up since the prevailing philosophy became one of releasing these people from institutions into the community. A 62 per cent reduction in psychiatric beds some 30 years ago was accompanied by levels of funding that simply weren’t enough to provide all the resulting community services needed. People without families to turn to, and with no social supports, tended to end up homeless. It has become a vicious circle – while mental health issues can lead to homelessness, homelessness also puts people at greater risk for mental illness. Because childhood trauma plays such a key role in chronic homelessness, it needs to be figured into the kinds of housing and support programs that are put in place for people who are homeless. Psychiatric supports should be among the programs that homeless shelters offer and should also be provided on a priority basis for people using the intervention program called Housing First. There is no doubt about the link between adverse childhood experiences and future mental health problems. People who have experienced at least four types of childhood trauma are 12 times more likely to have attempted suicide, seven times more likely to be alcoholic, and 10 times more likely to have injected street drugs. They are also much more likely to be violent. Interaction with the health-care and justice systems started early for the individuals surveyed in Calgary, aged between 18 and 80. Forty-two per cent of them had been foster children. Within the past year, 59 per cent had slept rough, 31 per cent had spent time in detox, 23 per cent had served jail time and 31 per cent had been in hospital. Eighty-two per cent regularly used alcohol, with 32 per cent using it daily and 70 per cent using drugs other than alcohol. Yet, the help that is available for the chronically homeless population is at best scattershot. More than 50 per cent of those surveyed who had received help for mental health and addiction issues said they didn’t get enough assistance. A quarter of those who didn’t receive treatment said they’d asked for help and hadn’t received it, while a third said long waitlists prevented them from accessing help. Many were in and out of a patchwork of programs with little to show for it. Solutions are not out of reach. Funding should target housing and case management programs designed to address the psychiatric issues resulting from childhood trauma. And Calgary’s network of community-based health care, housing and support programs should be expanded to help people suffering from multiple disorders. Currently, homeless shelters are serving as ad hoc institutions of mental health care for far too many people. With adequate funding and supports, long-term shelter users can be prioritized for psychiatric care, and shelters can return to their original mandate of being places where people who are temporarily homeless and in transition can get the help they need.